1999
DOI: 10.2116/analsci.15.365
|View full text |Cite
|
Sign up to set email alerts
|

Buffer Effect on the Photoelectrochemical Response of Bacteriorhodopsin

Abstract: Bacteriorhodopsin (bR) is the retinal protein functioning as a light-driven proton pump in Halobacterium salinarium. Photoisomerization of the retinal chromophore triggers the proton transport from the cytoplasmic side to the extracellular side of the membrane, and the electrochemical potential thus built up across the membrane is then used for ATP synthesis. 1 The proton transport is a cyclic process consisting of a series of intermediates, with lifetimes varying from picoseconds to milliseconds. 2,3 bR could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…2A,B. A similar observation was reported previously (23). In addition, when BR, a light‐driven H + pump, adsorbed on the electrode surface was replaced with halorhodopsin, a light‐driven Cl − pump, no light‐induced signals were observed.…”
Section: Resultssupporting
confidence: 90%
“…2A,B. A similar observation was reported previously (23). In addition, when BR, a light‐driven H + pump, adsorbed on the electrode surface was replaced with halorhodopsin, a light‐driven Cl − pump, no light‐induced signals were observed.…”
Section: Resultssupporting
confidence: 90%
“…A gradual magnitude decrease was observed in high buffer capacity as in the previous work . The decrease depends on buffer capacity and indicates that the electric signals are caused by pH change, which can be almost completely eliminated by adding a large amount of buffer, for instance, >50 mM for a thin AR4 film as shown in Figure b.…”
Section: Resultssupporting
confidence: 68%
“…A buffer can affect the amplitude and decay time of photoelectric signals. ,, It was shown with pH-sensitive dyes that buffers accelerate release of a proton from a membrane surface to the bulk . The present studies examine buffer effects via the photoelcterochemical approach.…”
Section: Resultsmentioning
confidence: 94%
“…To explain the buffer effect associated with the B2 component Liu et al assumed that the protons emitted into the solution during M formation protonated the buffer molecules, which were repelled or attracted ("positive" buffers or "negative" buffers, respectively) by the negative charge remaining on the membrane surface after proton release (Liu et al, 1991). Recently, Saga et al (1999) reported on the effect of buffers on the photoelectrochemical response of bR.…”
Section: Introductionmentioning
confidence: 99%